The Meaning of the Sanggring Tradition in Maintaining Social Solidarity in the Community of Gumeno Village, Gresik Regency - Hatta, Mulia Sakti Oki; Shodiq, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Sanggring tradition is a cultural tradition that continues to be preserved upon the 23rd of Ramadan, as a form of respect and obedience by the local community to a history that has been going on for centuries. The purpose of this study is to explain the meaning of the Sanggring tradition for the Gumeno community and how it serves as a medium for building solidarity within the Gumeno community. The research method used is a qualitative research method with a phenomenological approach, utilizing Emile Durkheim's theory of social solidarity as its analytical tool. Data collection techniques included interviews, participatory observation, documentation, and literature review. The data analysis technique used descriptive analysis. The results show that the meanings found in the Sanggring tradition are divided into three aspects: historical, spiritual, and social. Historically, the Sanggring tradition is closely related to the story of Sunan Dalem's journey and struggle. Spiritually, the Sanggring tradition symbolizes the community's gratitude to Allah SWT for Sunan Dalem's recovery. Socially and culturally, the Sanggring tradition serves as a means for the Gumeno community to maintain close ties with one another. The solidarity established in the Gumeno community is a mechanical solidarity formed from a shared belief that sanggring dishes can cure various ailments. This research can be beneficial for the Gresik Regency government in designing effective and participatory policies for cultural preservation. The novelty of this research lies in its emphasis on the specific social function of the sanggring tradition in enhancing social solidarity and the involvement of local government, a role that has not been widely explored in previous research.